2020
DOI: 10.1371/journal.pgen.1008665
|View full text |Cite
|
Sign up to set email alerts
|

Spastin mutations impair coordination between lipid droplet dispersion and reticulum

Abstract: Lipid droplets (LD) are affected in multiple human disorders. These highly dynamic organelles are involved in many cellular roles. While their intracellular dispersion is crucial to ensure their function and other organelles-contact, underlying mechanisms are still unclear. Here we show that Spastin, one of the major proteins involved in Hereditary Spastic Paraplegia (HSP), controls LD dispersion. Spastin depletion in zebrafish affects metabolic properties and organelle dynamics. These functions are ensured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 97 publications
0
32
0
Order By: Relevance
“…It is possible that increasing LD biogenesis simply expands the ER membrane, which has been shown to alleviate ER stress (Schuck et al, 2009). Consistent with this hypothesis is the observation that zebrafish lacking spastin are more susceptible to ER stress and displayed abnormal ER organization in sarcomeres (Arribat et al, 2020).…”
Section: Spastin M1 a Microtubule-severing Protein Is Recruited To Ldsmentioning
confidence: 85%
See 1 more Smart Citation
“…It is possible that increasing LD biogenesis simply expands the ER membrane, which has been shown to alleviate ER stress (Schuck et al, 2009). Consistent with this hypothesis is the observation that zebrafish lacking spastin are more susceptible to ER stress and displayed abnormal ER organization in sarcomeres (Arribat et al, 2020).…”
Section: Spastin M1 a Microtubule-severing Protein Is Recruited To Ldsmentioning
confidence: 85%
“…This phenotype was particularly prominent upon severe starvation, a condition that stimulates LD biogenesis (Rambold et al, 2015). An increased number of smaller LDs was also observed in cells derived from spastin KO fish embryos (Arribat et al, 2020). Overexpression of spastin M1 on the other hand induced the appearance of large, but fewer LDs (Papadopoulos et al, 2015;Arribat et al, 2020).…”
Section: Spastin M1 a Microtubule-severing Protein Is Recruited To Ldsmentioning
confidence: 90%
“…This reorganization subsequently disrupted spastin's ability to disperse LDs throughout the cell and aberrantly modulated neutral lipids and phospholipids on membranes throughout the muscle and brain (Arribat et al, 2020). Furthermore, embryonic zebrafish cells that were treated with oleic acid (a common method to induce LD formation) indicated that a loss of spastin resulted in a higher number of smaller LDs, therefore suggesting differential generation, and/or dispersion of LDs (Arribat et al, 2020). In addition to identifying potential new HSP biomarkers, this study also proposes that HSP-causing mutations impacts lipid profiles and LD networks.…”
Section: Hereditary Spastic Paraplegiamentioning
confidence: 99%
“…Spastin plays multiple roles in lipid metabolism at the level of the endoplasmic reticulum where lipids are produced for dispersal through the cell as lipid droplets. Spastin is a positive regulator of lipid metabolism through sorting lipid droplets from the endoplasmic reticulum [ 70 ], it coordinates lipid droplet dispersion and endoplasmic reticulum shape along microtubules [ 71 ], and tethers lipid droplets to peroxisomes [ 72 ].…”
Section: Future Directions: From Network To Drug Discoverymentioning
confidence: 99%